Clinical Characteristics of Non-Lactational Mastitis of Accessory Breast: A Case-Series Study - Zhao D; Zhang D; Zeng Y; Fu N; Xu X (International Journal of Women's Health, 2025)
Di Zhao,1,2 Dongxiao Zhang,1 Yifei Zeng,1,2 Na Fu,1 Xiaolong Xu1 1Department of Galactophore, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People’s Republic of China; 2Graduate School, Beijing University of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Dongxiao Zhang, Department of Galactophore, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, No. 23, Art Museum Back Street, Dongcheng District, Beijing, People’s Republic of China, Tel +86 13811077684, Email Tzdx_thinking@126.comBackground: Non-lactational Mastitis of Accessory Breast (NLM-AB) is a rare condition with limited research, leading to diagnostic challenges. Its clinical and demographic characteristics are poorly defined, and it is often confused with non-lactational mastitis (NLM), hindering effective diagnosis and treatment.Objective: This study aims to clarify the features of NLM-AB, distinguish it from NLM, and address key knowledge gaps to improve clinical diagnosis and patient management.Methods: We retrospectively analyzed data from 31 NLM-AB patients treated at Beijing Hospital of Traditional Chinese Medicine from January 2014 to September 2024. A 1:1 matched case-control study was conducted, comparing NLM-AB (case group) with 31 NLM patients (control group).Results: NLM-AB patients had a mean age of 36.68 ± 7.17 years and BMI of 23.10 ± 3.52. Most were married (83.87%) and had given birth (58.06%). All had axillary masses, with 85.19% showing skin changes. Statistically significant differences were found in marital status, reproductive history, breastfeeding duration, tumor size, and nipple retraction (P < 0.05). No significant differences were observed in nipple discharge, ulcer occurrence, or prolactin levels (P > 0.05).Conclusion: This study addresses a key clinical gap by identifying distinguishing features of NLM-AB, such as consistent axillary masses without nipple retraction and associations with reproductive history. These findings can directly support clinicians in early recognition and differential diagnosis of NLM-AB, avoiding unnecessary interventions targeting primary breast tissue. Incorporating these patient characteristics into diagnostic pathways may reduce misdiagnosis rates and guide more tailored treatment strategies, ultimately improving patient outcomes.Keywords: non-lactational mastitis, non-lactational mastitis of accessory breast, clinical characteristics, retrospective analysis, case series study